PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD DALAM MENINGKATKAN KETERAMPILAN BAHASA INDONESIA SISWA - Sari, Nydia Fatma; Abidin, Dindin; Faiz Ridlo, Azi (An-Nizam, 2024)
Indonesian language is one of the subjects in primary school, in this subject students are taught how to write, compose, read properly and accurately. In Karang Indah Village, the local language or Sundanese is more dominant than Indonesian. Indonesian language skills can be said to be low due to environmental factors. The author's goal in carrying out this activity is to empower the community, of course the students who are the target of this activity. Students are introduced to interactive learning media to improve Indonesian language skills. The method used in the implementation of the service is community education in the form of socialisation to students about Indonesian language, the importance of speaking Indonesian well, and how to write well. The learning media used is flashcard learning media to support students' Indonesian language skills at SDN Karang Indah 01. The results of learning activities using flashcard learning media greatly affect students' interest in learning and can improve students' skills in Indonesian. The introduction of interesting learning media makes students feel less bored in learning.